1999
DOI: 10.1002/(sici)1099-1573(199902)13:1<37::aid-ptr382>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of Indonesian medicinal plants on the infection of herpes simplex virus type 1

Abstract: Water and methanol extracts of 30 traditional medicinal plants, collected in Indonesia, were tested for their anti HSV‐1 activity. The extracts of eight plant species showed potent activity on the plaque assay at a concentration of 100 µg/mL. The therapeutic efficacy of seven selected plants was demonstrated by using a mouse HSV‐1 infection assay, both the methanol extracts of the fruit of Melaleuca leucadendron (Myrtaceae) and the pericarp of Nephelium lappaceum (Sapindaceae) significantly prolonged the devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…6,10,12,13,15) These compounds have been shown to act either in the early stage of adsorption or on virus surface structures thereby inhibiting penetration into susceptible cells. These modes of action favor the basis of the virucidal protocol as the more relevant approach for determining antiviral effect (eventually, prophylactic, where cells are treated before the infection).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6,10,12,13,15) These compounds have been shown to act either in the early stage of adsorption or on virus surface structures thereby inhibiting penetration into susceptible cells. These modes of action favor the basis of the virucidal protocol as the more relevant approach for determining antiviral effect (eventually, prophylactic, where cells are treated before the infection).…”
Section: Resultsmentioning
confidence: 99%
“…Melaleuca leucadendron and Nephelium lappaceum reduced mortality and delayed the appearance of lesions. 10) Among plant antiviral compounds, anthraquinones found in Aloe barbadensis inhibited HSV-1, HSV-2, varicela-zoster, pseudorabies and influenza.…”
mentioning
confidence: 99%
“…The roots, bark, and leaves have various uses in medicine and in the production of dyes. Previous studies have shown N.lappaceum rind extract to exhibit high antioxidant activity (Palanisamy et al, 2008), antibacterial activity (Thitilertdecha et al, 2010) and anti-Herpes Simplex virus type 1 (Nawawi A, 1999). Recently in our laboratory, N.lappaceum rind was also shown to have anti hyperglycemic potential (Palanisamy, Uma et al, 2011).…”
Section: Rind Of Rambutan Nephelium Lappaceum a Potential Source Ofmentioning
confidence: 99%
“…Nawawi et al (1999) tested the aqueous and methanolic leaf extracts of Plumbago zeylanica for anti-HSV-1 activity in the plaque reduction assay. Although different methods were used in that study, the methanol extracts of P. zeylanica at 91 ug/ml did not inhibit HSV-1 plaque formation in Vero cells.…”
Section: Resultsmentioning
confidence: 99%